2015
DOI: 10.1371/journal.pone.0121275
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Forest Fragmentation Affects Floral Visitors but Not the Structure of Individual-Based Palm-Pollinator Networks

Abstract: Despite increasing knowledge about the effects of habitat loss on pollinators in natural landscapes, information is very limited regarding the underlying mechanisms of forest fragmentation affecting plant-pollinator interactions in such landscapes. Here, we used a network approach to describe the effects of forest fragmentation on the patterns of interactions involving the understory dominant palm Astrocaryum mexicanum (Arecaceae) and its floral visitors (including both effective and non-effective pollinators)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…Applying meta-analytical techniques, Magrach et al (2014) demonstrated that the effects of fragmentation on mutualisms were primarily driven by habitat degradation, edge effects, and fragment isolation, with little effect of fragment size. Dattilo et al (2015) found that fragment size did not affect the topological structure of the individual-based palm-pollinator network. However, Aguirre and Dirzo (2008) reported pollinator abundance was negatively affected by fragment size.…”
Section: Discussionmentioning
confidence: 85%
“…Applying meta-analytical techniques, Magrach et al (2014) demonstrated that the effects of fragmentation on mutualisms were primarily driven by habitat degradation, edge effects, and fragment isolation, with little effect of fragment size. Dattilo et al (2015) found that fragment size did not affect the topological structure of the individual-based palm-pollinator network. However, Aguirre and Dirzo (2008) reported pollinator abundance was negatively affected by fragment size.…”
Section: Discussionmentioning
confidence: 85%
“…redundancy) in pollinator efficiency, sample under different abiotic conditions and use a range of sampling methods (e.g. collect entire inflorescences to sample beetles; Dáttilo, Aguirre, Quesada, & Dirzo, 2015).…”
Section: Objective 2: To Understand How Flower-visitor Communities mentioning
confidence: 99%
“…Furthermore, pollinators in deforested landscapes may occur in smaller number and be less effective than in forested landscapes (Dáttilo et al. ), representing a possible negative influence on the species gene flow distances and possibly driving related processes on the local scale (Breed et al. ).…”
Section: Discussionmentioning
confidence: 99%